Pyriform Sinus Fistula in the Fetus and Neonate: A Systematic Review of Published Cases - Chen, Tong; Chen, Jianglong; Sheng, Qingfeng; Zhu, Linlin; Lv, Zhibao (Frontiers in Pediatrics, 2020)
Purpose: To provide recommendations for the diagnosis and treatment of pyriform sinus fistula (PSF) in the fetus and neonate through a systematic review of the published literature. Methods: PubMed and Embase (1968–2019) were searched, and additional publications were obtained by searching the references by hand. The two reviewers assessed all papers and extracted the following variables: demographics, clinical features, diagnostic tests, interventions, and prognoses. Results: Forty-two papers were included, comprising a total of 158 cases. PSF presented almost exclusively on the left side (95.56%). Patients usually presented with a neck mass (100%) and respiratory distress (43.18%). The false-negative rate (FNR) of prenatal ultrasonography (US) was significantly higher than that of prenatal magnetic resonance imaging (MRI) (P < 0.01). For the diagnosis of PSF in neonates, computerized tomography (CT) and MRI were the most accurate diagnostic modalities. Ex utero intrapartum treatment (EXIT) was performed during delivery in 6 patients (26.09%). Among 135 patients with a reported date of definitive surgery, 117 (86.67%) underwent surgery during the neonatal period. Complications after definitive surgery appeared in 5 patients (3.16%), and all of them recovered spontaneously within 3 months. Furthermore, recurrence occurred in 4 patients (2.53%). Conclusion: In fetal cases with PSF suspected by US, MRI is necessary to confirm the diagnosis. During the neonatal period, patients with PSF typically present with a neck mass and respiratory distress, and CT/MRI appears to be the preferred diagnostic method. Definitive surgery is effective for treating neonatal PSF, with a low complication rate and low recurrence rate.